Genre in Selected Films by the Coen Brothers - Jezdinský, Jakub (Univerzita Pardubice, 2013)
The main purpose of this paper is to analyze film genres, their conventions, and their subsequent use in films Fargo and No Country for Old Men by the Coen Brothers. In the initial part of the paper the introduction and function of genre theory is presented. Specific concepts and definitions are further described. In the second part the Coen Brother's biography and their work are presented. The last part considers analysis of films with special attention being paid to the usage of genre conventions.
Žánry ve vybraných filmech bratří Coenů
Keywords: filmové žánry; bratři Coenové; Fargo; Tahle země není pro starý; film noir; western; film genre; Coen brothers; Fargo; No Country for Old Men; film noir; western